AI-DRIVEN EDUCATIONAL FINANCIAL GOVERNANCE : A SYSTEMATIC LITERATURE REVIEW ON THE TRANSFORMATION OF FINANCIAL MANAGEMENT AND RESOURCE ALLOCATION IN THE DIGITAL ERA - Ahmad Misbah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The digital transformation of educational institutions has necessitated a paradigm shift in governance, particularly in financial management. Traditional financial practices in educational institutions are increasingly inadequate in addressing the complexities of modern resource allocation, transparency, and sustainability. While the integration of Artificial Intelligence (AI) in education has predominantly focused on pedagogical enhancements, its application in educational financial governance remains underexplored. This study aims to systematically review the current literature on the integration of AI in educational financial management. Utilizing the PRISMA framework, a systematic search was conducted across major academic databases (Scopus, Web of Science, and DOAJ) for publications between 2019 and 2026. This review identifies three main dimensions of AI application: predictive budgeting and financial planning, automated auditing for transparency, and resource allocation optimization. Furthermore, the study highlights critical challenges, including data privacy concerns, algorithmic bias, and the digital divide among educational stakeholders. The research findings propose a conceptual framework for AI-driven financial governance, offering strategic insights for educational leaders to enhance financial sustainability and accountability. This review contributes to the paucity of literature on AI in educational administration and provides a roadmap for future empirical research.